Teaching Practice during the Pandemic Outbreak: Perceptions of Pre-Service English Teachers - Eka Fajar Rahmani (IJEE (Indonesian Journal of English Education), 2021)
ABSTRACTCurrent studies report that a teaching practice program is important for pre-service teachers of English in providing real teaching experiences at school. However, since the Covid-19 outbreak, all school activities are transferred to online delivery mode, which led to teaching practice implementation to be conducted online. This transference must cause pre-service teachers to have different teaching practice experiences. Therefore, the study aims to discover pre-service teachers' perceptions regarding their teaching practice experience during the pandemic. This research was conducted to 114 seventh-semester students of the English Education Department of FKIP Pontianak. The methodology was a mixed-method where the quantitative procedure was first done, followed by the qualitative procedure. The data were gathered through questionnaires and interviews. The results indicated that the online teaching practice program brought various experiences resulting in “satisfying” and “unsatisfying” perceptions. In detail, more than 50% of participants agreed that despite the challenging situations they faced during the practice, they found the online teaching practice program beneficial, especially in providing broad teaching insights and experience. Hence, despite limitations to its ways of implementation, teaching practice program tends to shape positive teaching mindset and attitudes for pre-service teachers. ABSTRAKStudi saat ini melaporkan bahwa program praktik mengajar penting bagi calon guru Bahasa Inggris dalam memberikan pengalaman mengajar yang nyata di sekolah. Namun, sejak merebaknya wabah Covid-19, seluruh kegiatan sekolah dialihkan secara online, sehingga pelaksanaan praktik mengajar dilakukan secara online. Pemindahan ini harus menyebabkan para calon guru memiliki pengalaman praktik mengajar yang berbeda. Oleh karena itu, penelitian ini bertujuan untuk mengetahui persepsi calon guru tentang pengalaman praktik mengajar mereka selama pandemi. Penelitian ini dilakukan terhadap 114 mahasiswa semester tujuh pada Jurusan Pendidikan Bahasa Inggris FKIP Pontianak. Metodolog yang digunakan adalah metode penelitian campuran di mana prosedur kuantitatif dilakukan pertama kali, diikuti oleh prosedur kualitatif. Pengumpulan data dilakukan melalui kuesioner dan wawancara. Hasil penelitian menunjukkan bahwa program praktik mengajar online memberi berbagai pengalaman yang menghasilkan persepsi “memuaskan” atau “tidak memuaskan”. Secara rinci, lebih dari 50% peserta setuju bahwa meskipun menghadapi situasi menantang selama praktik, mereka menemukan program praktik mengajar online bermanfaat, terutama dalam memberikan wawasan dan pengalaman mengajar yang luas. Oleh karena itu, dapat disimpulkan bahwa terlepas dari cara pelaksanaannya, program praktik mengajar selalu membentuk pola pikir dan sikap mengajar yang positif kepada guru prajabatan.